Efek Pertumbuhan Tanaman Bawang Merah (Allium cepa L.) pada Pemberian Kombinasi Biofertilizer Mikotrico (Mikoriza dan Tricoderma) - Qondhi, Anwar Asmoro; Isrianto, Pramita Laksitarahmi; Wilujeng, Sukian; Marmi, Marmi (UNIVERSITAS PGRI MADIUN, 2023)
Shallots (Allium cepa L.) are superior horticultural crops that have been intensively cultivated by farmers. Shallots contain nutrients and chemicals that have side effects on health. Farmers prefer to give environmentally friendly fertilizers, namely by giving biofertilizers compared to chemical fertilizers. Chemical fertilizers can tell an environmental story and are not good if consumed continuously. Biofertilizer fertilizer is very suitable for plants, such as onion cultivation which contains nutrients and active chemicals, many benefits for the body other than as a complementary seasoning. The onion growth process requires sufficient nutrients with the help of mycorrhizae and Tricoderma sp. The purpose of this study was to determine the effect of root and leaf growth of shallots on mycotrico (mycorrhizal and Tricoderma) biofertilizer fertilizers. This study was an experimental study and the research design used a completely randomized block factor design with 6 levels, namely 0%, 10%, 20%, 30%, 40%, and 50% Mikotrico with 5 replications. Based on the analysis using the ANOVA test, the results obtained (Î± = 0.00) number of roots, (Î± = 0.00) root length, while for plant height the Kruskal-Wallis test had a significant effect while the number of tunas had no significant effect. The application of mycotrico biofertilizer fertilizer at a dose of 30% had better growth in the number of roots, root length, and plant height of shallot (Allium cepa L.)